Pengaruh profitabilitas, leverage, likuiditas, struktur modal dan keputusan investasi terhadap nilai perusahaan pada perusahaan sektor keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Manalu, Peffi; Getsmani, Getsmani; Permatasari Hutagaol, Citra; Arisandy Aruan, Deasy (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to determine the effect of profitability, leverage, liquidity, capital structure, and investment decisions on firm value. A research approach is a quantitative approach. The study population was taken from financial sector companies that have been listed on the Indonesia Stock Exchange 2015-2017, namely from a total of 87 companies, 39 companies were taken. The sample applies the purposive sampling technique. The research successfully proves that profitability, leverage, liquidity, capital structure, and investment decisions have a positive and significant effect on firm value. Partially, the research results are only profitability which has a positive and significant effect on firm value. So that the Adj obtained. R Square 13.1% with the remaining 86.9% influenced by outside variables. Â